Growth performance of Nile tilapia fingerlings fed on yeast and yeast derivatives - Hisano, Hamilton; Narváez-Solarte, William Vicente Narváez; Barros, Margarida Maria; Pezzato, Luiz Edivaldo (Pesquisa Agropecuaria Brasileira, 2007)
The objective of this work was to assess growth perfomance and chemical-bromatological fillet composition of Nile tilapia fed on rations containing whole yeast, autolyzed yeast and yeast wall cell. Practical diets, isoproteic (32% of digestible protein), isoenergetic (3,200 kcal of digestible energy per kg) and supplemented by whole yeast (1, 2 and 3%), autolyzed yeast (1, 2 and 3%) and yeast cell wall (0.1, 0.2 and 0.3%), and a control diet without test ingredients were assessed. The experimental design was completely randomized, with ten treatments and four replicates. Animals fed on yeast and yeast derivatives supplemented diets showed enhanced growth performance compared to control. No difference on chemical-bromatological fillet composition was observed among contrast of totals of treatment. Yeast and yeast derivatives supplementation provided improvement on fish growth performance and inclusion of autolyzed yeast showed better growth performance when supplemented with 1.30 to 1.59%.